Comparative Analysis of Biomarkers in Cases of Pfizer and Sinopharm Covid19 Vaccination Effects - Abed, Ahmed Salim (Medical Science Journal for Advance Research, 2023)
Background: The rolling out of the heterogenous COVID-19 vaccines around the world warrants the recognition of their immunogenicity patterns and the details of any possible side effects. This study assesses the immune system’s effect with the Pfizer-BioNTech and Sinopharm BIBP Coronavirus vaccine. Methods: Within the context of the immunological biomarkers’ dataset which incorporated the C-Reactive Protein, the White Blood Cells, D-Dimers, granulocytes, platelets, and hemoglobin levels, the response profiles following vaccination were determined. The biomarkers were categorized into groups based on the deviation extent from the clinical reference ranges and matched the previously studied vaccine product recipients. Results: This research showed that both male and female patients who were given the Pfizer-BioNTech vaccine had significant protein inflammatory concentration increases which was greater than those patients who were injected with the Sinopharm BIBP vaccine indicating that the immune response to the former was more robust. Normal range values of WBC were maintained between vaccines on both cases and were slightly higher in the Pfizer-BioNTech cohort. D-Dimer levels increased in both vaccinees (Pfizer-BioNTech and Moderna), with the greatest averages in individuals receiving the Pfizer-BioNTech vaccine which might explain an increased propensity for clot formation though this was only a small threat medically. The number of granulocytes served as a reference and the counts were normal and steady for both the test and control groups, implying that the immune function remained unaffected. There was variability in platelet levels with the Pfizer-BioNTech category appearing slightly higher on average, however they were still all in the normal range. The correct hemoglobin levels were seen in both the vaccinated and unvaccinated groups a suggestion that there was no significant red cell activity influence by vaccines, none. Conclusion: The inflammatory reaction and the tendency for clots associated with the Pfizer-BioNTech vaccine are assured in higher levels while the Sinopharm BIBP vaccine appears to associate with somewhat lower levels. As well, whether these data will have clinical significance is rather controversial and controversies need to be resolved in the future. Whilst inter-batch biomarkers were also observed to vary, these remained within the normal physiological ranges, which implies a good safety profile for both vaccines. The monitoring and investigation of these cannot be overemphasized as they are the bases that help to understand well and to guarantee the long-run effectiveness and safety of vaccines for Covid-19.